2015
DOI: 10.1136/annrheumdis-2014-207150
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic focus score as a prognostic tool

Abstract: We would like to thank Dr Arnaud et al 1 for their comment on our article discussing the prognostic value of salivary gland assessments in primary Sjögren's syndrome ( pSS). 2 One of our findings was that having a lymphocytic focus score (LFS) ≥3 (number of foci/4 mm 2 ) at the time of diagnosis contributes significantly to the risk of lymphoma development during pSS disease course. We agree that the follow-up time after biopsy is important to take into account because differences observed could merely be a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…A complex interplay between these cells and their effector molecules results in chronic inflammation with B cell hyperactivity, auto-antibody production and ultimately formation of ectopic germinal centers [3,4]. Reflecting B cell hyperactivity,~30% of pSS patients develop extraglandular manifestations and 5-10% of patients with pSS develop B-cell lymphoma, in particular those patients with high numbers of lymphocytic foci or germinal centers [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A complex interplay between these cells and their effector molecules results in chronic inflammation with B cell hyperactivity, auto-antibody production and ultimately formation of ectopic germinal centers [3,4]. Reflecting B cell hyperactivity,~30% of pSS patients develop extraglandular manifestations and 5-10% of patients with pSS develop B-cell lymphoma, in particular those patients with high numbers of lymphocytic foci or germinal centers [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies concluded that the presence of GC in diagnostic biopsies was not predictive of MALT lymphoma development in SS patients (Haacke, van der Vegt et al, ; Johnsen et al, ; Kapsogeorgou et al, ), while others showed opposite results (Bombardieri et al, ; Sène et al, ; Theander et al, ). Lymphocytic focus score (LFS) ≥3, that is, ≥3 aggregates of 50 or more lymphocytes/4 mm 2 of glandular tissue, was found to be able to identify SS patients with an increased risk for lymphoma development (Carubbi et al, ; Risselada, Hair, Kruize, Bijlsma, & van Roon, ; Risselada et al, ). Similarly, elevated FcRL4+ expression (Haacke, Bootsma et al, ) and pSTAT‐3 expression (Ciccia et al, ) were reported in diagnostic biopsies of patients who developed MALT lymphoma, while weak or absent A20 staining was observed in the majority of patients with MALT lymphoma (Johnsen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…| 57 DELLI Et aL. 50 or more lymphocytes/4 mm 2 of glandular tissue, was found to be able to identify SS patients with an increased risk for lymphoma development Risselada, Hair, Kruize, Bijlsma, & van Roon, 2015;Risselada et al, 2014). Similarly, elevated FcRL4+ expression and pSTAT-3 expression (Ciccia et al, 2015) were reported in diagnostic biopsies of patients who developed MALT lymphoma, while weak or absent A20 staining was observed in the majority of patients with MALT lymphoma (Johnsen et al, 2016).…”
Section: (Continues)mentioning
confidence: 91%
“…They consist of segregated T and B cell zones and follicular dendritic cells within areas of activated and proliferating B cells. The formation of GC-like structures is accompanied by the ectopic production of the lymphoid chemokines CXC chemokine ligand 13 (CXCL13), C-C motif chemokine ligand 21 (CCL21) and CXCL12 [85,[93][94][95][96][97].…”
Section: Germinal Centers and Lymphoepithelial Lesionsmentioning
confidence: 99%
“…In 1993, Pennec et al [10] compared the accuracy of UWSF and others techniques used to assess xerostomia, including sialography, scintigraphy and salivary gland biopsy, among 40 individuals with pSS, 16 patients with secondary SS (sSS), 16 patients with connective tissue diseases and 14 healthy subjects. For pSS, the UWSF test exhibited 68% sensitivity, 81% specificity, a PPV of 90% and an NPV of 50% compared with sialography (74,87,93, and 41%, respectively), scintigraphy (75,75,90, and 45%, respectively) and salivary gland biopsy (95,75,90, and 14%, respectively). A multicenter study with 693 patients was conducted in 1993 to test the diagnostic criteria that were eventually included in the 2002 classification [11], and determined cut-off points for the unstimulated and stimulated WSF and the corresponding sensitivity and specificity.…”
mentioning
confidence: 97%